11β-Hydroxysteroid dehydrogenase type 2 complementary deoxyribonucleic acid stably transfected into Chinese hamster ovary cells: Specific inhibition by 11α-hydroxyprogesterone - Morita, H. (1996)
The 11β-hydroxysteroid dehydrogenase type 2 (11βHSD-2) enzyme is thought to confer aldosterone specificity upon mineralocorticoid target tissues by protecting the mineralocorticoid receptor from binding by the more abundant glucocorticoids, corticosterone and cortisol. We have developed a Chinese hamster ovary cell line stably transfected with a plasmid containing the rat 11βHSD-2 complementary DNA. This cell line has expressed the enzyme consistently for many generations. The 11βHSD-2 was located primarily in the microsomes, but significant amounts also existed in the nuclei and mitochondria. The enzymatic reaction was unidirectional, oxidative, and inhibited by the product, 11-dehydrocorticosterone, with an IC50 of approximately 200 nM. The K(m) for corticosterone was 9.6 ± 3.1 nM, and that for NAD+ was approximately 8 μM. The enzyme did not convert dexamethasone to 11-dehydrodexamethasone. Tunicamycin, an N-glycosylation inhibitor, had no effect on enzyme activity, 11α-Hydroxyprogesterone (11αOH-P) was an order of magnitude more potent a competitive inhibitor of the 11βHSD-2 than was glycyrrhetinic acid (GA) (approximate IC50 0.9 vs. 15 nM). 11βOH-P, progesterone, and GA were almost equipotent (IC50 = 10 and 6 nM, respectively), and 5α-pregnandione and 5β-pregnandione were less potent (IC50 = 100 and 500 nM, respectively) inhibitors of the enzyme. When the inhibitory activities were examined with intact transfected cells, 11αOH-P was more potent than GA (IC50 = 5 and 150 nM, respectively). 11αOH-P was not metabolized by 11βHSD-2. We were unable to demonstrate the presence of 11αOH-P in human urine. In conclusion, a cell line stably transfected with the rat 11βHSD-2 was created, and the enzyme kinetics, including inhibition, were characterized. 11αOH-P was found to be a potent relatively specific inhibitor of the 11βHSD-2 enzyme. Its potential importance is that it is the most specific inhibitor of the 11βHSD-2 so far encountered and would aid in the study of the physiological importance of the isoenzyme.